La Presión Arterial y el Nivel de Actividad Física en estudiantes universitarios - Chiluiza Yausin, Kevin David (2025)
This study addresses a topic of great relevance to public health and the well-being of students, since the relationship between physical activity and blood pressure is essential to prevent cardiovascular diseases in the long term. The quasi-experimental approach, which evaluates the effects before and after an intervention, is suitable for observing how a change in behavior (such as increasing physical activity) can influence a physiological variable such as blood pressure. The intervention appears to have a positive impact, particularly on diastolic blood pressure, which is encouraging since diastolic is a key indicator of heart and blood vessel health. However, the variability in results highlights the importance of considering individual factors such as genetics, prior physical fitness, and other lifestyle habits, which could influence how each student responds to physical activity. An interesting aspect of this study is its descriptive and propositional approach, as it not only analyzes the problem, but also suggests the need for adjustments in future interventions. It could be useful to incorporate personalized physical activity recommendations or design programs adapted to the level of each student to maximize the benefits on cardiovascular health.